The Role of Indoor Plants in air Purification and Human Health in the Context of COVID-19 Pandemic: A Proposal for a Novel Line of Inquiry - El-Tanbouly, Rania; Hassan, Ziad; El-Messeiry, Sarah (Frontiers in Molecular Biosciences, 2021)
The last two decades has seen the discovery of novel retroviruses that have resulted in severe negative consequences for human health. In late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged with a high transmission rate and severe effects on human health with 5% infected persons requiring hospitalisation and 3.81 million deaths to date globally. Aerosol particles containing virions are considered the main source of SARS CoV-2 transmission in this pandemic with increased infection rates in confined spaces. Consequently, public, and private institutions had to institute mitigation measures including the use of facial masks and social distancing to limit the spread of the virus. Moreover, the role of air purification and bio-decontamination is understood as being essential to mitigate viral spread. Various techniques can be applied to bio-decontaminate the air such as the use of filtration and radiation; however, these methods are expensive and not feasible for home use. Another method of air purification is where indoor plants can purify the air by the removal of air pollutants and habituated airborne microbes. Indoor plants could prove to be a cost-efficient way of indoor air-purification that could be adapted for a variety of environments with no need for special requirements and can also add an aesthetic value that can have an indirect impact on human health. In this review, we will discuss the emergence of the COVID-19 pandemic, and the currently used air purification methods, and we propose the use of indoor plants as a new possible eco-friendly tool for indoor air purification and to reduce the spread of COVID-19 in confined places.